Translation as a Course: A View of Indonesian EFL Postgraduate Students’ Attitude - Akhmad Baihaqi (NOTION: Journal of Linguistics, Literature, and Culture, 2022)
The objective of this research is to investigate the Indonesian EFL Postgraduate students’ attitudes towards the course of translation. The researcher used a case study method by managing observation, interview, and questionnaire to collect the data. The questionnaire contained 30 items concerning students’ attitudes in terms of behavioral, cognitive, and emotional aspects. The participants in this present study were 11 students of the English Education Department of Postgraduate degree at a public university in Banten Province, Indonesia. The results indicate that the students hold positive attitudes toward the existence and the learning process of the translation course. These can be verified from the results of questionnaires which show that the average scores of positive attitudes for behavioral, cognitive, and emotional aspects consecutively are 74.3%, 80.6%, and 84.4%. These positive attitudes are not only affected by the lecturer-student interaction, but also by the cooperative learning atmosphere and experience that the lecturer and students manage while having a teaching and learning process of translation. Since attitudes can be modified by the experience, the effective translation teaching and learning process can encourage students to be more positive towards the translation course they are involved in.